2007
DOI: 10.1177/0883073807307091
|View full text |Cite
|
Sign up to set email alerts
|

Rett Syndrome: Prevalence Among Chinese and a Comparison of MECP2 Mutations of Classic Rett Syndrome With Other Neurodevelopmental Disorders

Abstract: Rett syndrome is an X-linked dominant neurodevelopmental disorder. Mutation of the methyl-CpG-binding protein 2 gene (MECP2) is present in up to 96% of patients with Rett syndrome. Eight mutations represent the hotspot of MECP2 mutations (R106W, R133C, T158M, R168X, R255X, R270X, R294X, and R306C) in patients with classic Rett syndrome. The prevalence and survival rate of Rett syndrome among Chinese women was investigated. The 8 hotspot mutations and the A140V mutation were also studied in 4 cohorts of Chinese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 21 publications
0
24
0
Order By: Relevance
“…Cases were usually ascertained through a single contact with specialists (14-18, 25, 27), child health departments (22, 23, 28) or education departments(15, 27), institutions (14, 25) and special schools(14, 15, 24, 26), although some used population-based sources (19-21). In one study, case ascertainment involved contacting laboratories for MECP2 positive individuals or analysis of pre-collected blood from a family RTT organization (13), and only cases with a pathogenic MECP2 mutation were included.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cases were usually ascertained through a single contact with specialists (14-18, 25, 27), child health departments (22, 23, 28) or education departments(15, 27), institutions (14, 25) and special schools(14, 15, 24, 26), although some used population-based sources (19-21). In one study, case ascertainment involved contacting laboratories for MECP2 positive individuals or analysis of pre-collected blood from a family RTT organization (13), and only cases with a pathogenic MECP2 mutation were included.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (20, 27) varied in their ascertainment methods, inclusion criteria, measures of frequency, sample size and methods of analysis, making comparisons difficult. For example exclusion of mutation negative (13) or atypical cases (27) could partly explain why the prevalence in France (0.58 per 10,000 females aged 4-15 years) (13) and Hong Kong (0.57 per 10,000 females 35 years or younger) (27) were only two thirds that in Australia (0.88 per 10,000 females aged 5-18 years) (20). …”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of RTT in 1.19/10,000 in females younger than 18 years registered in Serbia is similar to that observed in Scotland and Sweden [5,24], which is higher than in those registered in the USA (Texas, North Dacota), Japan, Estonia, Switzerland and Hong Kong [6,7,8,9,10,25], and lower than in regions of Norway and Northern Italy [11,26]. …”
Section: Discussionmentioning
confidence: 86%
“…Survival rate analysis showed that 89% of Serbian RTT patients survive up to 12 years of age, while in Texas the survival rate among the 20 year olds was 94% [12]. Additionally, in Hong Kong, there were no lethal outcomes before the age of 10 in RTT population [25]. …”
Section: Discussionmentioning
confidence: 99%
“…), while it was reported as 0.58 per 10 000 mutation‐negative females in France (Bienvenu et al . ) and 0.57 per 10 000 females in atypical cases in Hong Kong (Wong & Li ). Generally, after a period of normal development, a healthy‐looking baby girl falls into developmental stagnation, which is followed by rapid deterioration, loss of acquired speech and the replacement of the purposeful use of hands with incessant stereotypies, a characteristic of the syndrome (Chahrour & Zoghbi ).…”
Section: Introductionmentioning
confidence: 99%